Arbutin Protects Retinal Pigment Epithelium Against Oxidative Stress by Modulating SIRT1/FOXO3a/PGC-1α/β Pathway - Tang, Han; Du, Han; Kuang, Xielan; Huang, Hao; Zeng, Jingshu; Long, Chongde; Zhu, Binbin; Fu, Licheng; Wang, Hua; Zhang, Qingjiong; Lin, Shuibin; Yan, Jianhua; et al. (Frontiers in Genetics, 2022)
Age-related macular degeneration (AMD), as the leading cause of blindness among the elderly in western societies, is majorly accompanied with retinal pigment epithelium (RPE) degeneration. Due to the irreversible RPE cell loss among oxidative stress, it is crucial to search for available drugs for atrophic (dry) AMD. RNA-Seq analysis revealed that genes related to aging and mitochondrial health were differentially expressed under Arbutin treatment while compared to oxidative injury, our study demonstrated that Arbutin substantially abrogated oxidative stress-induced cell senescence and apoptosis linked to intracellular antioxidant enzyme system homeostasis maintenance, restored mitochondrial membrane potential (MMP) and reduced the SA-β-GAL accumulation in RPE. Furthermore, Arbutin alleviated oxidative stress-mediated cell apoptosis and senescence via activation of SIRT1, as evidenced by the increase of the downstream FoxO3a and PGC-1α/β that are related to mitochondrial biogenesis, and the suppression of NF-κB p65 inflammasome, whereas rehabilitation of oxidative stress by SIRT1 inhibitor attenuated the protective effect of Arbutin. Finally, we validated the results in an in vivo model constructed by NAIO3-injured mice. OCT and HE staining showed that Arbutin sustained retinal integrity in the case of oxidative damage in vivo, and the disorder of RPE cytochrome was alleviated through Fundus observation. In summary, our findings identified that oxidative stress-induced mitochondrial malfunction and the subsequent cells senescence acceleration in RPE cell, while Arbutin inhibited TBHP-induced RPE degeneration via regulating SIRT1/Foxo3a/PGC-1α/β signaling pathway. These findings suggested Arbutin to be a new agent with potential applications in the development of age-related macular degeneration disease.